2017
DOI: 10.1021/acs.nanolett.7b03476
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Local Strain Vector in Atomic-Layered MoSe2 by Second-Harmonic Generation

Abstract: Strain serves as a powerful freedom to effectively, reversibly, and continuously engineer the physical and chemical properties of two-dimensional (2D) materials, such as bandgap, phase diagram, and reaction activity. Although there is a high demand for full characterization of the strain vector at local points, it is still very challenging to measure the local strain amplitude and its direction. Here, we report a novel approach to monitor the local strain vector in 2D molybdenum diselenide (MoSe) by polarizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
137
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 143 publications
(148 citation statements)
references
References 50 publications
8
137
2
1
Order By: Relevance
“…Mechanic strain is an effective way to alter the electronic and optical properties by deforming the crystal lattice . Recently, strain has been proved as an effective method to engineer the NLO . For instance, a monolayer MoS 2 under a strain is no longer belongs to D 3 h space group and the χ (2) tensor has more than one independent components.…”
Section: Modulation and Enhancement Of Nlomentioning
confidence: 99%
See 4 more Smart Citations
“…Mechanic strain is an effective way to alter the electronic and optical properties by deforming the crystal lattice . Recently, strain has been proved as an effective method to engineer the NLO . For instance, a monolayer MoS 2 under a strain is no longer belongs to D 3 h space group and the χ (2) tensor has more than one independent components.…”
Section: Modulation and Enhancement Of Nlomentioning
confidence: 99%
“…Liang et al demonstrated that the strain can not only change the angle dependence pattern, but also change the total SHG intensity. They reported a ~49% intensity change for 1% strain . In addition, SHG modulation of bilayer MoSe 2 was realized by applying a strain on the underneath monolayer.…”
Section: Modulation and Enhancement Of Nlomentioning
confidence: 99%
See 3 more Smart Citations